(untitled) (Bulletin of Armenian Libraries, 2025)
The purpose of the article is to show the Armenian-French cultural, historical and political ties during the First World War of 1915. In particular, for the assistance provided by the French navy during the Armenian self-defense battles and for the great humanitarian attitude. All this found its place in the form of facts in the memoirs of Sh. T. Tekeyan, a marine of Armenian origin, who was directly involved in the rescue of Armenians. The memoirs were published in Paris in 1919 and, after many years of oblivion, translated from French into Armenian. Other publications about that period and events were also included in the article.